Acute promyelocytic leukemia: evaluation of diagnostic tests from 2000 to 2018 in a public hospital - Aline C. Hey; Ana Paula Azambuja; Yara Carolina Schluga; Elenaide C. Nunes; Rodrigo Miguel Bendlin; Valderez R. Jamur
ABSTRACT Introduction: Acute promyelocytic leukemia (APL) is caused by t(15;17)(q24;q21) translocation, which product is the fusion oncoprotein PML-RARa (promyelocytic leukemia-retinoic acid receptor alpha). The morphology of leukemic promyelocytes is usually characteristic, with the presence of faggot cells and coarse cytoplasmic granulations; immunophenotype is characteristic in most cases. However, definitive laboratory diagnosis should be performed by detecting t(15;17) or by PML-RARa fusion protein. Objectives: To compare cytomorphology, flow cytometry, and classical cytogenetic of bone marrow samples from patients with APL, treated at the Complexo Hospital de Clínicas da Universidade Federal do Paraná (CHC-UFPR), as well as describe the possible discrepancies between the methodologies. Method: Retrospective analysis of APL cases treated at the CHC-UFPR from January 2000 to July 2018. Results: Eighty-eight patients (42 man/ 46 woman; mean age: 34 years), 42.1% of them presented a high-risk prognosis. Flow cytometry was performed in 83 cases (94.3%); karyotype was performed in 79 cases (89.7%), but translocation t(15;17) was confirmed in only 53 cases (60.2%). From the 28 patients with a non-conclusive karyotype; fourteen (15.9%) of them presented the PML-RARa transcript in the molecular analysis. In total, 35 patients (39 8%) performed research of the PML-RARa gene by molecular biology. Only 45 patients (51.1%) presented concordant diagnosis among the three technical exams (morphology, flow cytometry and cytogenetics). Overall survival was 67% at 4.8 years, with 29 deaths. Conclusion: Genetic confirmation was observed in 76.1% of samples, 60.2% by conventional cytogenetics and 15.9% by molecular biology. There was a disagreement between the methodologies, and a low sensibility of the conventional cytogenetics, demonstrating the importance of performing molecular techniques for diagnostic confirmation.